2022
DOI: 10.47405/mjssh.v7i2.1271
|View full text |Cite
|
Sign up to set email alerts
|

Mengenal pasti Faktor Personaliti ‘Big Five’ Terhadap Prestasi Pembelajaran: Satu Kajian Sistematik

Abstract: Tret personaliti ‘big five’ diterima pakai dalam semua kajian personaliti yang terlibat dalam kajian psikologi sosial dan telah menghasilkan banyak artikel yang meliputi aspek psikologi, sains pendidikan, teknologi dan pelbagai aspek yang lain. Tujuan kajian ini dijalankan adalah untuk melakukan tinjauan secara sistematik terhadap perhubungan antara tret personaliti ‘big five’ dan pencapaian akademik pelajar. Selain daripada itu, kajian ini bertujuan untuk mengenal pasti tret personaliti yang paling dominan me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Personality also influences students' behavior in several facets of their lives, such as the relationship between a subject or topic of interest in school (Vedel, 2016). Many research used the 'Big Five' model to investigate the association between personality traits and student academic accomplishment, and this study successfully found the 'Big Five' personality's strength in assessing student academic achievement (Zali & Surat, 2022). Personality is the arrangement of factors such as biology, psychology, and sociology, and it is this element that enables a person to have a personality or character.…”
Section: Personality Big Fivementioning
confidence: 87%
See 3 more Smart Citations
“…Personality also influences students' behavior in several facets of their lives, such as the relationship between a subject or topic of interest in school (Vedel, 2016). Many research used the 'Big Five' model to investigate the association between personality traits and student academic accomplishment, and this study successfully found the 'Big Five' personality's strength in assessing student academic achievement (Zali & Surat, 2022). Personality is the arrangement of factors such as biology, psychology, and sociology, and it is this element that enables a person to have a personality or character.…”
Section: Personality Big Fivementioning
confidence: 87%
“…Furthermore, the trajectory of student engagement in STEM remains static, with participation never exceeding 50% compared to the targeted 60% (Idris et al, 2023a). According to Zali and Surat (2022), openness to cognitive and non-cognitive experiences manifests itself in a variety of interests, a desire to discover new and unexpected life events, and a sense of pleasure. Conscientiousness is a personality trait that focuses on concerns including orientation, habitual behavior, and impulse control.…”
Section: Personality Big Fivementioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies on personality and performance focus on students' academic achievement (Kamilah & Zurina, 2019;Begum et al, 2021;Wang et al, 2023). The findings of the study obtained by Zali and Surat (2022) which found that all the five factors of personality traits which is neuroticism, openness, conscientiousness, agreeableness and extraversion have different effects on the academic achievement of students.…”
Section: Introductionmentioning
confidence: 99%